Evaluating the quality of hybrid learning in higher education: stakeholder perspectives from a Chinese university - Yalan, Huang; Marcial, Dave E. (Frontiers in Education, 2025)
In the contemporary era of rapid technological advancements, hybrid learning has become a significant educational model, particularly in higher education institutions. This study investigates how administrators, teachers, and students in a Chinese university evaluate hybrid learning across nine domains: leadership and management, staffing profile and professional development, review and improvement, resources, student information and support, student experience, curriculum design, assessment and integrity, and learning outcomes. A cross-sectional survey was administered online to 341 respondents (60 administrators, 70 teachers, and 211 students). Descriptive statistics summarized ratings, while the Kruskal–Wallis test examined group differences. Findings show administrators rated hybrid learning most favorably (mean = 3.02), followed by teachers (mean = 2.84) and students (mean = 2.59) on a 4-point scale. Significant differences (p < 0.05) emerged across all domains. Significant differences were observed among the groups, particularly in technological competency, institutional readiness, and hybrid learning quality, with students indicating lower satisfaction in leadership (mean score of 2.49) and staffing (mean score of 2.57). Despite these discrepancies, most respondents rated hybrid learning as high across the majority of domains. The study concludes that, while hybrid learning at the university meets essential quality indicators, further enhancements are necessary to address disparities and optimize overall learning outcomes.